Sumber Daya Alam dan Pembangunan: Sebuah Perspektif Komparatif - Seda, Francisia (UI Scholars Hub, 2006)
The relationship between natural resources and development in the so-called developing world is important. The question posed in this paper is how do the different types of natural resources; oil, LNG, and forests affect the broader environment-development relations? This study shows that the presence of natural resources especially the oil and LNG industries played a major role in the Indonesian national development. In the context of Evans conceptual continuum, Indonesia has both the elements of predatory and developmental state viewed from the environment-development relations.